EXPLORING SOCIAL-EMOTIONAL LEARNING THROUGH NETFLIX MOVIE ENOLA HOLMES (2020) LESSONS AND IMPLICATION FOR EFL EDUCATION - Simron Krisnuarjati Hindom; Edeltrudis Patrisia Soge; Natalina Antonia dos Santos; Ouda Teda Ena; Concilianus Laos Mbato (Widya Mandala Surabaya Catholic University, 2025)
This Study explores the integration of Social-Emotional Learning (SEL) with the Netflix movie Enola Holmes (2020), focusing on its relevance and implications for EFL educational contexts. Based on SEL's five core competencies as defined by CASEL (Collaborative for Academic, Social, and Emotional Learning), including self-awareness, self-management, social awareness, relationship skills, and responsible decision-making. The study applied a qualitative descriptive design, with thematic content analysis, to examine how the SEL competencies are seen in the film’s main character, Enola Holmes, throughout the narrative. Using the film and its script as primary data sources, key scenes and dialogues were coded and analysed to identify SEL indicators. The findings reveal that Enola Holmes, as the main character, constantly expresses the five core components of Social-Emotional Learning (SEL) through her collaborative skills, moral reasoning, and independent decision-making. Therefore, the study suggests that integrating popular media like Enola Holmes into educational settings can enhance the delivery of SEL core competencies, specifically with regard to the implications in educational settings by offering a contextually meaningful, relatable, and engaging medium for students. The study contributes to the limited body of research that connects SEL and film analysis, emphasizing the value of visual storytelling in the educational environment. It highlights how popular media can be harnessed to cultivate emotional intelligence and character development in classroom settings.